THE ROLE OF CONTEXTUAL TASKS IN FORMING THE SELF-DEVELOPMENT COMPETENCE OF FUTURE CHEMISTRY TEACHERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the aspects of improving the methodology for developing self-development competence of future chemistry teachers. Contextual teaching technologies play an important role in increasing the effectiveness of education in the educational process. In this approach, students are directly connected to the topics and develop skills in applying knowledge in practice. The conclusions based on the analysis of the literature by the author reveal the possibilities of effective teaching based on improving the methodology for developing self-development competence of future chemistry teachers.